Corruption in state contracting: A co-responsibility of the business sector still pending - Gil Pedreros, Ivon Dayann (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The Corruption Perceptions Index 2021 places Colombia among the worst countries in the management of public resources worldwide, a situation that has been repeated over the last ten years, suggesting that public policies and legal tools are insufficient to prevent corruption. misuse of the treasury. Despite the above, the participation of companies in reducing acts of corruption is only voluntary and is focused on a preventive stage, which is not promoted by the Colombian State.